Multicellular "hotspots" harbor high-grade potential in lower-grade gliomas. Issue 1 (8th February 2021) - Kirby, Alastair J; Lavrador, José P; Bodi, Istvan; Vergani, Francesco; Bhangoo, Ranjeev; Ashkan, Keyoumars; Finnerty, Gerald T
Abstract: Background: Lower-grade gliomas may be indolent for many years before developing malignant behavior. The mechanisms underlying malignant progression remain unclear. Methods: We collected blocks of live human brain tissue donated by people undergoing glioma resection. The tissue blocks extended through the peritumoral cortex and into the glioma. The living human brain tissue was cut into ex vivo brain slices and bathed in 5-aminolevulinic acid (5-ALA). High-grade glioma cells avidly take up 5-ALA and accumulate high levels of the fluorescent metabolite, Protoporphyrin IX (PpIX). We exploited the PpIX fluorescence emitted by higher-grade glioma cells to investigate the earliest stages of malignant progression in lower-grade gliomas. Results: We found sparsely distributed "hot-spots" of PpIX-positive cells in living lower-grade glioma tissue. Glioma cells and endothelial cells formed part of the PpIX hotspots. Glioma cells in PpIX hotspots were IDH1 mutant and expressed nestin suggesting they had acquired stem-like properties. Spatial analysis with 5-ALA-conjugated quantum dots indicated that these glioma cells replicated adjacent to blood vessels. PpIX hotspots were formed in the absence of angiogenesis. Conclusion: Our data show that PpIX hotspots represent microdomains of cells with high-grade potential within lower-grade gliomas and identify locations where malignant progression could start.